Español - Saeteros Hernández, Rosa Del Carmen (2022)
The Behavioral change PRECEDE-PROCEDE model, created by Lawrence Green and Marshall Kreuter in 1980, It is based on the study of sexual education needs, designing, implementation and evaluation of actions for promoting sexual and reproductive education. Objetive: To adjust the model to the demands and university context. Methods: Technological development research, based on the classic PRECEDE – PROCEDE model. Results: The PRECEDE - PROCEDE model incorporates the necessary approaches to the complexity, breadth and nuances required by the study of a transdisciplinary topic such as the promotion of sexual and reproductive health. It is a classic, dynamic, holistic, educational, multidisciplinary model that observes carefully the details and gives as a result a continuous analysis, which takes into account the determinants with a broader vision, without isolating the person from their context, with a certain point of view that considers the social complexity , according to an ecological model, is not linear, nor mechanical, but flexible and susceptible to adjustments and concomitant use of other alternatives, in search of finding the best way to solve the problem, allows the participation of those involved in all phases ; in the multidisciplinary diagnosis: social, epidemiological, behavioral and lifestyle, educational, political and administrative; in the design, implementation and evaluation of processes, results and impact. Conclusions: The PRECEDE - PROCEDE model incorporates the necessary approaches to the complexity, breadth and nuances required by the study of a transdisciplinary topic such as the promotion of sexual and reproductive health.